2019
DOI: 10.1027/1866-5888/a000226
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Leader–Member Exchange and Employees’ Proactive Behaviors

Abstract: Abstract. The present study proposed that, unlike prior leader–member exchange (LMX) research which often implicitly assumed that each leader develops equal-quality relationships with their supervisors (leader’s LMX; LLX), every leader develops different relationships with their supervisors and, in turn, receive different amounts of resources. Moreover, these differentiated relationships with superiors will influence how leader–member relationship quality affects team members’ voice and creativity. We adopted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(35 reference statements)
1
6
0
Order By: Relevance
“…Because Profile 5 refers to very high levels of PsyCap, individuals with that profile should not transit, supported by high LMX. These results align with previous research that showed positive associations of LMX with various job-and personality-related variables, such as proactive behaviors ( Lai et al, 2019 ) and resilience, a core mechanism of PsyCap ( Kakkar, 2019 ). Similarly, research has also noted that LMX features, such as trust and proximity, can also enhance one’s PsyCap ( Law et al, 2010 ; Kakkar, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Because Profile 5 refers to very high levels of PsyCap, individuals with that profile should not transit, supported by high LMX. These results align with previous research that showed positive associations of LMX with various job-and personality-related variables, such as proactive behaviors ( Lai et al, 2019 ) and resilience, a core mechanism of PsyCap ( Kakkar, 2019 ). Similarly, research has also noted that LMX features, such as trust and proximity, can also enhance one’s PsyCap ( Law et al, 2010 ; Kakkar, 2019 ).…”
Section: Discussionsupporting
confidence: 91%
“…In meta-analytic research, Martin et al (2016) have shown that a high-quality LMX relationship is essential for the attitudes and performance of employees. For instance, LMX has been found to be related to employees’ proactive behavior ( Lai et al, 2019 ), engagement and job satisfaction ( Volmer et al, 2011 ; González-Navarro et al, 2019 ), as well as their resilience ( Kakkar, 2019 ). Moreover, González-Navarro et al (2019) found a positive association between LMX and job engagement.…”
Section: An Applied Examplementioning
confidence: 99%
“…However, on the one hand, abusive supervision might result in a low exchange relationship (e.g. low leader-member exchange) with employees (Xu et al , 2011), implying low leader support and minimum resources for employees from leaders (Lai et al , 2019). On the other hand, dealing with an abusive leader requires that employees spend their physical and cognitive efforts and resources (Nandkeolyar et al , 2014), and thus they are less likely to join new projects.…”
Section: Discussionmentioning
confidence: 99%
“…In general, leaders fill an important place in most employees' working time, because they represent the organization in rewarding and assigning work (Bélanger et al , 2016; Peyton et al , 2019), and employees often spend much time interacting with the leader, for example, when negotiating or communicating their voice or creative solution (Lai et al , 2019). Thus, according to the JD-R model and the definition of job demands, leaders who exhibit abusive supervision can be viewed as representing the social and organizational aspects of job demands, which continuously deplete employees' efforts at a high psychological cost.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Second, the basis for establishing SSGX is emotional factors. Leaders have limited time and energy, so not every subordinate has the opportunity for in-depth interaction with leaders [ 48 ], especially emotional communication. Employees must understand the demands of leaders and know their preferences in order to gain their trust and become their leaders’ “in-group” members [ 49 ].…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%